Studies on losartan novel extrudates design and evaluation to treat hypertension - Putta Rajesh Kumar, Jagannath M, Earshad Md, Gowtham K.K, Hafsa M, Shanta Kumar S.M. (Journal of Applied Pharmaceutical Science)
Mini matrices containing Losartan potassium as a model drug were prepared by extrusion method using Hydroxy propyl methyl cellulose as matrix materials with or without xanthan gum and carbopol, and combination of xanthan gum and carbopol and propylene glycol as plasticizer. The prepared mini matrices were further evaluated for surface texture, uniformity of diameter, thickness, weight, moisture content, drug content uniformity, drug-excipients interaction, relative swelling, mucoadhesive test, in vitro drug release pattern. All the HPMC mini matrices showed good swelling which is proportional to concentration of polymer. The In vitro release of drug was in the range of 64.83% to 93.66%. Formulation H1 prepared with a drug-polymer ratio of 1:0.5 (LSP:HPMC) and 5% propylene glycol by weight of polymer as plasticizer showed promising results as a controlled release dosage form and released approximately 93.66% of the drug in 12 h. This study proves that extrusion method can be used for designing controlled release drug delivery systems providing nearly zero-order drug release over a period of 12 h.
Keywords: Losartan, Extrusion, Mini matrices, In vitro studies, Release kinetics.